Research on the Mechanisms Driving and Strategic Choices for Enterprise ESG Transformation in the Context of Green Financial Policy Constraints - Zhang, Jinrui; Che, Yixuan; Wang, Jiaxin; Wang, Xinnuan; Liu, Xin (Pinnacle Academic Press Proceedings Series, 2026)
Under the constraints of green financial policies, enterprise environmental, social, and governance (ESG) transformation has become a core pathway for achieving sustainable development. Policy instruments such as green credit, green bonds, differentiated interest rates, risk assessment frameworks, and ESG-related disclosure requirements encourage firms to integrate ESG factors into strategic planning, investment decisions, and daily operations. Existing research shows that green financial policies can significantly improve corporate ESG performance, with particularly pronounced effects in highly polluting industries and financially developed regions where regulatory pressure and market expectations are stronger. Policy-driven transformation is typically realized through the optimization of production and operational processes, the adoption of low-carbon and energy-saving technologies, and the construction of green and resilient supply chains. In parallel, digital transformation provides data infrastructure, real-time monitoring, and risk management tools that support ESG target setting, performance tracking, and transparent reporting, thereby enhancing environmental performance and market competitiveness. Nonetheless, enterprises still face challenges, including uneven access to green financial resources, heterogeneous policy implementation, inconsistent ESG information disclosure standards, and shortages of professional ESG and digital talent. Looking ahead, it is crucial to strengthen policy coordination and guidance, refine evaluation and incentive mechanisms, promote technological and digital innovation, and improve training systems. These efforts will help enterprises build systematic and effective ESG management frameworks, better align financial and sustainability objectives, and ultimately achieve a balanced integration of economic, environmental, and social value.